IJM 2020
DOI: 10.34196/ijm.00210
|View full text |Cite
|
Sign up to set email alerts
|

French do it better. The distributive effect of introducing French family fiscal policies in Italy

Abstract: Italy has one of the lowest fertility rates in the world. A solution, often advocated to incentivize fertility, could be to reform the Italian tax and benefit system taking inspiration from the French fiscal family treatment. This would imply to introduce the quotient system, where taxation is not on an individual basis, as in Italy, but the tax applies to the family as a whole, and to introduce the cash-benefits provided in France to families. The purpose of our paper is to assess the distributive effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…More ambitious papers try to calculate both supply and demand effects of the COVID-19 crisis on different occupations and industries ( Maria del Rio-Chanona et al, 2020 ). Moreover, an incipient literature considers measures of inequality when computing effects on employment ( Brunori et al, 2020 ) and “teleworkable” occupations ( Bonavida Foschiatti & Gasparini, 2020 ; Irlacher & Koch, 2020 ; Palomino et al, 2020 ).…”
Section: Conceptualizing the Potential To Teleworkmentioning
confidence: 99%
“…More ambitious papers try to calculate both supply and demand effects of the COVID-19 crisis on different occupations and industries ( Maria del Rio-Chanona et al, 2020 ). Moreover, an incipient literature considers measures of inequality when computing effects on employment ( Brunori et al, 2020 ) and “teleworkable” occupations ( Bonavida Foschiatti & Gasparini, 2020 ; Irlacher & Koch, 2020 ; Palomino et al, 2020 ).…”
Section: Conceptualizing the Potential To Teleworkmentioning
confidence: 99%
“…Many studies in this nexus for European countries identified a decline in income inequality from january 2020 to january 2021 (Brunori et al, 2020 andBrewer andTasseva 2021). The reason behind this negative relation is explained by these studies is that, as there existed differences in losses of the households but Italian government launched many schemes for compensation which targeted the poor not the rich people?…”
Section: Introductionmentioning
confidence: 99%